"Barbell Sign": A Diagnostic Imaging Finding in Progressive Multifocal Leukoencephalopathy. Issue 4 (July 2018) - Bezuidenhout, A. Fourie; Andronikou, Savvas; Ackermann, Christelle; Du Plessis, Anne-Marie; Basson, Derik; Bhadelia, Rafeeque A.
Abstract : Abstract: The recently proposed diagnostic algorithm for progressive multifocal leukoencephalopathy underscores the importance of imaging and emphasizes the role of the radiologist in the diagnostic workup. We describe a case series of patients with visual symptoms and a typical pattern of brain involvement in definite progressive multifocal leukoencephalopathy, for which we have coined the term barbell sign .